Praças : funções e inter-relações - Soares, Igor Norbert (2007)
The research studies the existing conflicts in the urban way where the squares are inserted, investigating that it forms influence the circulation, use and accessibility of this environment. The square is an element of great space, historical, social and ambient importance, configuring itself as vital space for the events of the public life and improvement of the urban environmental. The study was accomplished in the city of Cruz Alta - RS, where there are no publications on squares with the inclusion and the proposed focus, in spite of the existence of several research lines in many cities of the country and of the world the about of this subject. The idea of this study is to work with central and local squares, making a register of each space of leisure of the city in order to generate a pré-diagnosis of Cruz Alta squares. A case study was accomplished at two squares of the city, investigating aspects physical, environmental, of use and accessibility. They were accomplished bibliographical research on the theme and field research with observations of the physical aspects of the squares and I spill, environmental measurements and the users investigation through maps of behavior and questionnaires. The results will contribute to a better understanding of the characteristics of Cruz Alta squares, besides the relationship square - user, generating information to come to subsidize future interventions in the analyzed spaces and in other areas